Not Convinced: Lecturers' Conceptions of Quality Assurance - Sullivan, Hugh (2012)
This dissertation is an investigation into how lecturers' conceptions of quality differ from the way quality is constructed by the quality assurance systems and procedures responsible for it. Lecturers opinions about these systems are also explored.